Observational Study Regarding Two Bonding Systems and the Challenges of Their Use in Orthodontics: An In Vitro Evaluation - Sorana Maria Bucur; Anamaria Bud; Adrian Gligor; Alexandru Vlasa; Dorin Ioan Cocoș; Eugen Silviu Bud (Applied Sciences, 2021)
The purpose of this in vitro study was to analyze and identify a methodology for the improvement of the shear bond strength of orthodontic brackets bonded with two orthodontic adhesive systems considered to be widely used, Transbond Plus Color Change with Transbond Plus Self-Etching Primer and Fuji Ortho LC with orthophosphoric acid under various enamel conditions: dry, moistened with water and moistened with saliva. The sample size included a group of 120 freshly extracted premolars distributed into six study groups, each one of 20 teeth. A universal testing machine was used to detach the brackets. We determined and compared the strength of the two studied adhesive systems used in different enamel surface conditions. The mean shear bond strength values in groups 1 (TPCC, TSEP, dry), 2 (TPCC, TSEP, water), 3 (TPCC, TSEP, saliva), 4 (Fuji Ortho LC, etched, dry enamel), 5 (Fuji Ortho LC, etched enamel, water) and 6 (Fuji Ortho LC, etched enamel, saliva) were 15.86, 12.31, 13.04, 15.27, 14.14 and 13.11 MPa, respectively. ANOVA test and Student’s t-test showed significant differences between groups. While clinically acceptable shear bond strengths were obtained for all six studied groups, a particular outcome that to the authors’ knowledge has not been documented elsewhere has been obtained: in case of water contamination, it is preferable to use Fuji Ortho LC instead of Transbond Plus.